2021
DOI: 10.3390/jof7020138
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Genetic Transformation System in Guanophilic Fungus Amphichorda guana

Abstract: Fungi from unique environments exhibit special physiological characters and plenty of bioactive natural products. However, the recalcitrant genetics or poor transformation efficiencies prevent scientists from systematically studying molecular biological mechanisms and exploiting their metabolites. In this study, we targeted a guanophilic fungus Amphichorda guana LC5815 and developed a genetic transformation system. We firstly established an efficient protoplast preparing method by conditional optimization of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Stable osmotic pressure is the critical factor for protoplasts to regenerate cell walls [ 31 ]. In this study, the osmotic pressure stabilizers 1 M sucrose and 1.2 M sorbitol were tested for protoplast regeneration in ANM regeneration medium with the optimized protoplast formation system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable osmotic pressure is the critical factor for protoplasts to regenerate cell walls [ 31 ]. In this study, the osmotic pressure stabilizers 1 M sucrose and 1.2 M sorbitol were tested for protoplast regeneration in ANM regeneration medium with the optimized protoplast formation system.…”
Section: Resultsmentioning
confidence: 99%
“…Taking the economy and efficiency into consideration, we found that 1 M sucrose is more suitable as the osmotic pressure stabilizer for the protoplast regeneration of both strains. Stable osmotic pressure is the critical factor for protoplasts to regenerate cell walls [31]. In this study, the osmotic pressure stabilizers 1 M sucrose and 1.2 M sorbitol were tested for protoplast regeneration in ANM regeneration medium with the optimized protoplast formation system.…”
Section: Establishment Of Protoplast Preparation and Transformationmentioning
confidence: 99%
“…This transformation efficiency was prominent in the entire mushroom transformation system (Table 1). High-quality protoplasts lay the foundation for successful transformation [37]. During the enzymatic hydrolysis of hyphae, lysozyme reduces protoplast viability, especially when using excessive amounts of lysozyme or extended reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…Protoplast preparation and PEG−mediated transformation were performed as protocols as previously described [32] with some modifications. The purified protoplasts were resuspended in 3 mL 1× STC sorbitol and estimated using a hemocytometer (XB.…”
Section: Generation Of Gene Deletion Mutantsmentioning
confidence: 99%